2014
DOI: 10.1007/s10147-013-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent employment trend of childhood cancer survivors in Japan: a cross-sectional survey

Abstract: The unemployment rate is not high in Japan, but some CCSs need extended disability qualification. The independent factors related to unemployment were late effects and dropping out of school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
1
21
1
1
Order By: Relevance
“…Previous studies on factors linked with childhood cancer survivors' unemployment have rarely explored the long-term effects as a potential determinant. However, developing physical late effects has been found to increase the risk of unemployment [16,19,20,29]. In contrast, we found no factor related to the survivor's history of AL to indicate a higher risk of unstable employment for the survivors in our study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous studies on factors linked with childhood cancer survivors' unemployment have rarely explored the long-term effects as a potential determinant. However, developing physical late effects has been found to increase the risk of unemployment [16,19,20,29]. In contrast, we found no factor related to the survivor's history of AL to indicate a higher risk of unstable employment for the survivors in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Concerning occupational outcomes, most of the studies conducted have reported higher rates of unemployment among childhood cancer survivors than among their siblings or the population as a whole [4,6,[13][14][15][16][17][18]. Factors found to be associated with unemployment risk in the survivor population are both demographic (current age, female gender, interrupted schooling, lower education) [16,17,19,20] and cancerrelated (younger age at diagnosis, treatment with cranial irradiation, somatic late effects) [13,14,[16][17][18][19][20][21][22]. However, when childhood cancer survivors obtain employment, the literature on their occupational achievements is rather sparse.…”
Section: Introductionmentioning
confidence: 94%
“…Despite these findings, the associated factors of CCS worries have not been sufficiently evaluated in Japan. We previously conducted a cross‐sectional survey of CCS in Japan to clarify employment status . In the current study, we re‐analyzed these data in order to identify worries and their associated factors.…”
supporting
confidence: 82%
“…As reported in the previous study, CCS with brain tumor or bone/soft‐tissue sarcoma had significant high and severe late effects . It is commonly assumed that most CCS have some late effects, which has a negative impact on psychosocial outcomes .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation